Facilitators of uncertainty in decision-making in Iranian nurses: A qualitative study - Mitra Mousavi Shabestari; Faranak Jabbarzadeh Tabrizi; Fariborz Roshangar; Vahid Zamanzadeh; Akram Ghahramanian; Parvin Sarbakhsh (Kashan University of Medical Sciences, 2022)
Background: Many nurses are uncertain when making clinical decisions, and this can lead to burnout and professional dissatisfaction. However, no study has addressed facilitators of uncertainty in clinical decision-making among Iranian nurses. Objectives: This study aimed to explore Iranian nurses' experiences of facilitators of uncertainty in decision-making. Methods: This qualitative content analysis study was conducted from June to December 2020. Participants were 17 nurses with bachelor's or higher degrees who were purposively recruited from three hospitals affiliated with Tabriz University of Medical Sciences. Data were collected through semi-structured interviews and analyzed through a content analysis method. Results: Participants' experiences were categorized into three main categories, namely, an unconfident nurse, complex situations, and unclear guidelines and policies. Each category included three to four subcategories. Conclusion: Nurses may experience uncertainty in clinical decision-making when confronted with ambiguous clinical situations or lack sufficient decision-making skills. Nurse leaders are suggested to develop educational programs and support interventions to promote nurses' decision-making skills and help them manage ambiguous situations.